Internship contracts in Spain: A stepping stone or a hurdle towards job stability? - Sara de la Rica; Lucía Gorjón (SERIEs - Journal of the Spanish Economic Association, 2022)
Internship contracts (ICs) were designed as a stepping stone for educated young workers to develop their professional skills upon graduation. Such contracts incentivise employment creation, as firms benefit from lower wages and tax reductions, but at the same time, firms are expected to develop training programmes to improve the professional skills of youth. This paper assesses whether such subsidies help improve the labour market trajectories of the beneficiaries of ICs. To do so, we focus on entrants into the labour market and compare those who start through an IC with a matched control group whose first employment episode is through a nonsubsidised temporary contract. We look at short, medium and long-term effects on job stability and wages. We find that in the short run, labour market performance, in terms of wages and job stability, is poorer for the beneficiaries of the IC, unless they leave the firm right after the IC experience. In the medium and long run, however, the negative impact on wages is mitigated, and its impact on job stability is positive. A possible interpretation is that firms, in the short run, use ICs to lower hiring costs, but beneficiaries send a positive signal to the market that is rewarded in the medium and long terms.
Keywords: D04; J08; J13; 330; Active labour market policies; Employment; Evaluation; Internship contract; Subsidies; Youth